Content of Polycyclic Aromatic Hydrocarbons in the Road Asphalt in Olecko - Ireneusz Chrząścik; Magdalena Szymalska; Mariusz Kluska (Studia Ecologiae et Bioethicae, 2008)
Przedstawiono ocenę zawartości wielopierścieniowych węglowodorów aromatycznych (WWA) w asfaltach drogowych wyprodukowanych w różnych latach na terenie Polski. Zwrócono uwagę na zagrożenia wynikające podczas kontaktu z asfaltem Estimation of Polycyclic Aromatic Hydrocarbons (PAHs) in the road asphalt produced in different years in Poland was presented. Attention was paid especially to risks resulting from contact with asphalt and negative influence on life and health of road users. All 5 hydrocarbons recognized by WHO as compounds with carcinogenic activity and have been found in investigated samples, t t e results are situated between 0.1 and 60 pg/kg of dry mass. Simultaneously, it is necessary to emphasize, that asphalt consist of 90 % of aggregates and 10% ofbinder which contains these analyzed compounds.